Ethical Governance in the Metaverse: Defining Accountability and Digital Citizenship in Virtual Societies (Journal of Ethics in Emerging Technologies & Society p-ISSN 3117-5996 and e-ISSN 3117-6003, 2025)
The emergence of the Metaverse—a convergence of augmented reality (AR), virtual reality (VR), and blockchain-based environments—has transformed digital interaction into a multidimensional experience. As millions of users engage in virtual economies, social spaces, and governance systems, the ethical and regulatory frameworks of these immersive ecosystems remain largely undefined. This paper explores the challenges of establishing ethical governance, ensuring accountability, and shaping digital citizenship in the Metaverse. By examining philosophical, technological, and policy dimensions, it investigates how identity, property, and social behavior translate into virtual spaces. The study emphasizes the urgent need for a moral framework that ensures safety, inclusivity, and justice within digital societies